2021
DOI: 10.3389/fonc.2021.686962
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prevention of Viral Hepatitis-Related Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common cancer in the world, and its incidence is increasing yearly. Hepatitis B virus (HBV) infection and hepatitis C virus (HCV) infection are important causes of HCC. Liver cirrhosis, age, sex, smoking and drinking, and metabolic risk factors will increase the risk of cancer in HBV/HCV patients. And viral load, APRI, FIB-4, and liver stiffness can all predict the risk of HCC in patients with viral infection. In addition, effective prevention strategies are essential in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 157 publications
(163 reference statements)
0
18
0
Order By: Relevance
“…HCC is caused by several genetic and environmental factors. Among these, large proportion of HCC cases occurred because of viral infection [ 11 ]. HCV-mediated HCC prevalence is increasing globally specifically in developing countries [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC is caused by several genetic and environmental factors. Among these, large proportion of HCC cases occurred because of viral infection [ 11 ]. HCV-mediated HCC prevalence is increasing globally specifically in developing countries [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, large proportion of HCC cases occurred because of viral infection [ 11 ]. HCV-mediated HCC prevalence is increasing globally specifically in developing countries [ 11 ]. The major problem in most cancers is the early detection.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in gender distribution is thought to be closely related to hormone levels in men and their unhealthy lifestyles like overworking, staying up late and excessive drinking. Third, in terms of smoking status, studies have shown that smoking is a minor risk factor for HCC [ 30 , 31 ]. According to reports, smoking can increase the morbidity and mortality of HCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset of HCC is frequently observed in patients with high alcohol intake and chronic viral hepatitis B or C infection, accounting for greater than 50% of cases [ 4 ]. Prevention of hepatitis-induced HCC occurs through prevention of exposure, inoculation with the hepatitis B vaccine (currently there is no hepatitis C vaccine), and/or treatment with targeted antiviral medications [ 5 ]. The expansion of vaccine inoculation in the United States, which was incorporated into the infant inoculation schedule in 1991, has greatly reduced the risk of hepatitis and cancer related mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%